Detection of Edwardsiella tardain catfish (Clarias sp.)by fluorescent antibody technique (FAT) - Firma, .; Amalia, Rahman Rizky; Sari, Utami; Chusbul, Chotimah; Siregar, Abdulgani Amri (Indonesian Society of Scientific Aquaculture (ISSA), 2012)
The fluorescent antibody technique (FAT) can be used to detectEdwardsiellatarda rapidly. As prelimenary step, it have been performed purity test of bacteria by PCR, specificity test of mouse anti-E. tarda monoclonal antibody by blocking using chicken and rabbit serum, and optimization of conjugate secondary antibody mouse IgG-H&L (FITC) dillution rate. Fourty eights catfish were intraperitoneally injected by 0,3 mL of E. tarda with different concentration, namely: 102 CFU/mL, 103 CFU/mL, 105 CFU/mL. Kidney, spleen, and liver from three fishes in each treatment were collected at interval time of six hours, 12 hours, 24 hours, 48 hours after infection. The results showed that E. tarda could be detected in fish infected with 102 CFU of E. tarda after six hours of injection in kidney,liver, and spleen of infected fish. Hence, FAT is faster than detection by bacterial culture method, and this technique can be useful to prevent the spread of fish disease. Keywords: fluorescent antibody technique, Edwardsiella tarda, detection, catfish